The existence of Red Junglefowls (Gallus gallus) in oil palm plantations in selected states in Malaysia and their morphological characteristics - Syahar A. A. G. (2021)
An investigation was carried out to establish the existence of Red Junglefowl (Gallus gallus) populations in oil palm plantations and to study their morphological characteristics. This study which commenced from February to August in 2009 and 2010, took place in several oil palm plantations in the state of Johor, Selangor and Pahang, Malaysia. Twenty seven Red Junglefowls which comprised of seven adult males, six adult females, four juvenile males, three juvenile females, four male chicks and three female chicks were successfully captured throughout this study using the scoop netting method. The morphological study highly suggested the purity of the birds based on the characteristics exhibited. The birds were characterised by boat-shape body appearance, white or red ear lobe and slender greyish blue leg. Thus, this study offered some evidence that oil palm plantations are found to be suitable in sustaining and providing ample survivability for the species to exist in the future.